2019
DOI: 10.1029/2019ms001845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CABLEv2.3.4 Land Surface Model Coupled to NU‐WRFv3.9.1.1 in Simulating Temperature and Precipitation Means and Extremes Over CORDEX AustralAsia Within a WRF Physics Ensemble

Abstract: The Community Atmosphere Biosphere Land Exchange (CABLE) model is a third-generation land surface model (LSM). CABLE is commonly used as a stand-alone LSM, coupled to the Australian Community Climate and Earth Systems Simulator global climate model and coupled to the Weather Research and Forecasting (WRF) model for regional applications. Here, we evaluate an updated version of CABLE within a WRF physics ensemble over the COordinated Regional Downscaling EXperiment (CORDEX) AustralAsia domain. The ensemble cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…For each case study, an offline spinup of 30 years of the hydrological state variables within CABLE was performed using the 3‐hourly Princeton meteorological forcing (Sheffield et al, 2006). Further details of the CABLE land surface model configuration used here is available in Hirsch, Kala, et al (2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each case study, an offline spinup of 30 years of the hydrological state variables within CABLE was performed using the 3‐hourly Princeton meteorological forcing (Sheffield et al, 2006). Further details of the CABLE land surface model configuration used here is available in Hirsch, Kala, et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Through the NASA Land Information System (LIS; Kumar et al, 2006;Peters-Lidard et al, 2007) the Australian Community Atmosphere Biosphere Land Exchange (CABLE) land surface model is coupled to NU-WRF. This coupled model environment is referred to as WRF-LIS-CABLE (Hirsch, Kala, et al, 2019). WRF-LIS-CABLE has been used previously to understand land-atmosphere interactions over Australia focusing both on extremes (Hirsch et al, 2014) and sensitivity to land cover change (Hirsch et al, 2015).…”
Section: Model Descriptionmentioning
confidence: 99%
“…In our study, a coupled leaf-canopy model (PROSAIL) produced forward runs over a wide range of realizations, and these were used as a training dataset to develop estimates of LAI using a random forest (RF) approach. The inversion of the forward runs needed to derive LAI was based on the REGularized canopy reflectance model (REGFLEC; Houborg et al, 2015), which has been shown to be suitable for largely automated applications (Houborg and McCabe, 2016). The configuration of REGFLEC in this study followed Houborg and McCabe (2018a) but using only the model inversion results (e.g., PROSAIL) due to a lack of in situ LAI data in the larger region of Al Jawf.…”
Section: Vegetation Indices and Biophysical Parametersmentioning
confidence: 99%
“…All simulations were carried out using the Noah land surface model (Chen and Dudhia, 2001), which is the most commonly used and extensively evaluated land surface model in WRF. Given that WRF is sensitive to physical parameterization options over both SEA and SWWA (Evans et al, 2012;Hirsch et al, 2019b;Kala et al, 2015a), we ran three ensembles to sample model structural variability (Table 1) based on these studies. The first ensemble used the Yonsei University planetary boundary layer (PBL) scheme with Monin-Obukhov similarity for the surface layer (Hong et al, 2006), the Rapid Radiative Transfer Model (RRTM) scheme for longwave radiation (Mlawer et al, 1997), the Dudhia scheme for shortwave radiation (Dudhia, 1989), and the Kain-Fritsch scheme for convection (Kain, 2004).…”
Section: Model Description and Experimentsmentioning
confidence: 99%
“…The second ensemble differs from the first by using the Mellor-Yamada-Janjic PBL scheme with ETA scheme for the surface layer (Janjić, 1994), and the third ensemble differs from the first ensemble by using the Betts-Miller-Janjic scheme for convection (Betts and Miller, 1986). We do not carry out additional model evaluation against observations in this paper, as all these WRF configurations, which all use the Noah land surface model, have already been extensively evaluated over both SEA and SWWA by numerous studies against maximum and minimum temperature and precipitation observations, and shown to reproduce the observed climatology reasonably well (Andrys et al, 2016(Andrys et al, , 2015Di Virgilio et al, 2019;Evans et al, 2012;Evans and McCabe, 2010;Firth et al, 2017;Hirsch et al, 2019aHirsch et al, , 2019cKala et al, 2015a).…”
Section: Model Description and Experimentsmentioning
confidence: 99%